COVID-19 and the Use of Masks by Children. Statement From the Association of Schools of Public Health in the European Region and the European Academy of Paediatrics - Lopes, Henrique; Middleton, John; De Guchtenaere, Ann; Hadjipanayis, Adamos (Frontiers in Pediatrics, 2021)
Despite the fact that the use of masks and respirators in adults has already reached a consensus in almost all countries and for situations in which they are recommended, this is not the case for the use of mask by children. This statement, regarding the usage of mask by children, has been jointly produced by the Association of Schools of Public Health in the European Region (ASPHER) and the European Academy of Paediatrics (EAP). It provides recommendations on the size of the mask, the material and ergonomics of children's masks. The authors also discuss the psychological dimension of children when they are asked to wear a mask. Moreover, they tackle the difficulties of children with disabilities.